Structural and biochemical characterization of the folyl-poly-γ-l-glutamate hydrolyzing activity of human glutamate carboxypeptidase II - Navrátil, Michal; Ptáček, Jakub; Šácha, Pavel; Starková, Jana; Lubkowski, Jacek; Bařinka, Cyril; Konvalinka, Jan (The FEBS journal, 2014)
In addition to its well-characterized role in the central nervous system, human glutamate carboxypeptidase II (GCPII; Uniprot ID Q04609) acts as a folate hydrolase in the small intestine, participating in the absorption of dietary polyglutamylated folates (folyl-n-γ-l-glutamic acid), which are the provitamin form of folic acid (also known as vitamin B9 ). Despite the role of GCPII as a folate hydrolase, nothing is known about the processing of polyglutamylated folates by GCPII at the structural or enzymological level. Moreover, many epidemiologic studies on the relationship of the naturally occurring His475Tyr polymorphism to folic acid status suggest that this polymorphism may be associated with several pathologies linked to impaired folate metabolism. In the present study, we report: (a) a series X-ray structures of complexes between a catalytically inactive GCPII mutant (Glu424Ala) and a panel of naturally occurring polyglutamylated folates; (b) the X-ray structure of the His475Tyr variant at a resolution of 1.83 Å; (c) the study of the recently identified arene-binding site of GCPII through mutagenesis (Arg463Leu, Arg511Leu and Trp541Ala), inhibitor binding and enzyme kinetics with polyglutamylated folates as substrates; and (d) a comparison of the thermal stabilities and folate-hydrolyzing activities of GCPII wild-type and His475Tyr variants. As a result, the crystallographic data reveal considerable details about the binding mode of polyglutamylated folates to GCPII, especially the engagement of the arene binding site in recognizing the folic acid moiety. Additionally, the combined structural and kinetic data suggest that GCPII wild-type and His475Tyr variant are functionally identical.
Keywords: Models, Molecular; stabilita enzymů; kyselina polyglutamová; Enzyme Stability; Hot Temperature; Humans; Antigens, Surface; Binding Sites; Crystallography, X-Ray; vazebná místa; Polymorphism, Genetic; antigeny povrchové; polymorfismus genetický; Glutamate Carboxypeptidase II; glutamátkarboxypeptidasa II; Polyglutamic Acid; krystalografie rentgenová; molekulární modely; vysoká teplota; Kinetics; kinetika; lidé